Strategies to Build Students' Moderate Attitude Through the Cultivation of Ahlusunnah Values Waljamaah Annahdliyah (Descriptive study at SMP Plus Maarif NU Ciamis and SMP Plus Maarif NU Pangandaran) - Maftuh Salam; Ulfiah; Didin Wahidin; Ujang Nurjaman (IJGIE (International Journal of Graduate of Islamic Education), 2022)
The emergence of intolerant radical Islamic groups, who are easy to heresy, disbelieve in other groups, can even lead to hostility and conflict against other groups who disagree, is a trend of intolerance and radicalism in Indonesia that tends to increase. Kecenderungan ini dipengaruhi beberapa factor terutama kontestasi politik, ceramah atau pidato bermuatan ujaran kebencian di media social (medsos) dan media lainnya. Tujuan penelitian ini adalah untuk memperoleh gambaran tentang strategi membangun sikap moderat peserta didik melalui penanaman nilai-nilai ahlusunnah waljamaah annahdliyah di sekolah menengah pertama. This study uses a qualitative approach with descriptive methods and data collection techniques through interviews, observations, and document studies. The results showed that the strategy to build a moderate religious attitude of students was carried out through the cultivation of Aswaja An Nahdliyah values based on school culture. and Islamic boarding schools that adhere to the teachings of Islam Ahlussunnah Waljamaah An Nahdliyah through the values of Tawasuth (moderate), 'Itidal (straight/fair), Tasamuh (tolerance) and Tawazun (balance) through strategic steps a) providing knowledge with a model (rationalization) through Aswaja learning, b). Habituation, and c) Extracurricular Pagar Nusa, d) Good interaction and communication between teachers and students and e) Charismatic approach, (Suritauladan) with the cohesiveness of all ranks in the two schools.